Navigating fertility, reproduction and modern contraception in the fragile context of South Kivu, Democratic Republic of Congo: 'Les enfants sont une richesse'. Issue 3 (4th March 2019) - Dumbaugh, Mari; Bapolisi, Wyvine; Bisimwa, Ghislain; Mwamini, Marie-Chantale; Mommers, Paula; Merten, Sonja
Abstract: Modern contraception has created new possibilities for reimagining reproductive norms and has generated new socio-cultural uncertainties in South Kivu province, Democratic Republic of Congo. Using inductive analysis of women's reproductive narratives, this paper explores how women in a high fertility context encounter and integrate recently introduced family planning and modern contraceptive education and services into their lives. As foundational socio-cultural norms confront the new reproductive possibilities offered by contraception, power dynamics shift and norms are called into question, re-interpreted and re-negotiated. Reproduction is located as a socially constructed process at the intersection of fertility norms, power dynamics, institutional practices, embodied realties and personal desires. In many ways the possibilities created by contraception – meant to increase certainty in the lives of users – actually increase uncertainty. The complexity of reproductive navigation reveals the shortcomings of reproductive theory and health and development discourses which view women and men as autonomous decision makers, removing them from the multiplicity of influencing factors, histories and power dynamics within which they realise their reproductive lives.